Effect of dietary Quebracho tannin extract on feed intake, digestibility, excretion of urinary purine derivatives and milk production in dairy cows. Issue 1 (2nd January 2017) - Henke, Anika; Dickhoefer, Uta; Westreicher-Kristen, Edwin; Knappstein, Karin; Molkentin, Joachim; Hasler, Mario; Susenbeth, Andreas
ABSTRACT: The aim of this study was to evaluate the effects of dietary Quebracho tannin extract (QTE) on feed intake, apparent total tract digestibility (ATTD), excretion of urinary purine derivatives (PD) and milk composition and yield in dairy cows. Fifty Holstein cows were divided into two groups. To reach a similar performance of both groups, cows were divided according to their milk yield, body weight, days in milk and number of lactations at the start of the experiment averaging 33.2 ± 8.2 kg/d, 637 ± 58 kg, 114 ± 73 d and 2.3 ± 1.6 lactations, respectively. The cows were fed a basal diet as total mixed ration containing on dry matter (DM) basis 34% grass silage, 32% maize silage and 34% concentrate feeds. Three dietary treatments were tested, the control (CON, basal diet without QTE), QTE15 (basal diet with QTE at 15 g/kg DM) and QTE30 (basal diet with QTE at 30 g/kg DM). Two treatments were arranged along six periods each 21 d (13 d adaptation phase and 8 d sampling phase). The ATTD of DM and organic matter were reduced only in Diet QTE30, whereas both QTE treatments reduced ATTD of fibre and nitrogen (N), indicating that QTE impaired rumen fermentation. Nevertheless, feed intake was unaffected by QTE. In Diet CON, urinary N excretion accounted for 29.8% of N intake and decreased in treatments QTE15 and QTE30 to 27.5% and 17.9%, respectively. Daily faecal N excretion increased in treatments CON, QTE15 and QTE30 from 211 to 237 and 273 g/d, respectively, which amounted to 39.0%, 42.4% and 51.7% of the N intake, respectively. Hence, QTE shifted N excretion from urine to faeces, whereas the proportion of ingested N appearing in milk was not affected by QTE (average 30.7% of N intake). Daily PD excretion as indicator for microbial crude protein (CP) flow at the duodenum decreased in treatment QTE30 compared with Diet CON from 413 to 280 mmol/d. The ratios of total PD to creatinine suggest that urinary PD excretion was already lower when feeding Diet QTE15 . While there was no effect of Diet QTE15, treatment QTE30 reduced milk yield, milk fat and protein. Both QTE treatments reduced milk urea concentration, which suggest that ruminal degradation of dietary CP was reduced. In summary, adding QTE at dosages of 15 and 30 g/kg DM to diets of lactating dairy cows to improve feed and protein use efficiency is not recommended.